The Role Of Religiousity Leadership As A Moderation Of Factors Affecting Organization Performance After Publish Of The Minister Of BUMN Number SE-7/MBU/07/2020 - Mardinata Rusli, Yohanes (DINASTI RESEARCH, 2024)
The effectiveness of an organization in achieving its vision, mission, and organizational goals cannot be separated from the role of its leader. The role of the leader can be seen from his leadership style. This study aims to analyze the role of religious leadership of a leader in strengthening or weakening the factors that influence the performance of BUMN companies with the banking industry sector. The factors that influence the performance of an organization are seen from the servant leadership, organizational culture, and work ethic of the company.This study uses a quantitative method with primary data obtained from the distribution of questionnaires that will be carried out in this study to respondents who are employees working at State-Owned Enterprises in the Banking Industry sector with an assessment for their superiors in the department where they currently work. This study uses samples that have been collected or returned from both physical questionnaires and digital questionnaires with google forms consisting of 159 BUMN employees working in the banking sector who are domiciled in the cities of Jakarta and Bandung as respondents from 170 questionnaires distributed. The results of the study indicate that Servant Leadership and Organizational Culture have a positive effect on organizational performance. However, work ethic does not affect organizational performance. Religiousity Leadership can moderate the influence of Servant Leadership and Organizational Culture on Organizational Performance. However, Religiousity Leadership cannot moderate the influence of work ethic on organizational performance. This research contributes to organizational management, especially State-Owned Enterprises in the banking sector so that they can improve their organizational performance after the publication of the Circular Letter from the Ministry of BUMN